Casa de velación - Bolaños García, Estefanía (2017)
La Mariscal Sucre is a neighborhood that has experienced an important growth in the city of Quito, where also its built heritage has been lost by the lawlessness that has been consolidated, causing a series of problems that affect the quality of life of its inhabitants. Ninth semester AR0960 (2016) workshop, suggests several strategies that respond to the current situation in the sector. One of them is the implementation of equipment and facilities that provide to users services and benefits according to their needs. The Vigil House is part of the proposed equipment plan, and arises from the lack of funeral services in the northern part of La Mariscal. The project, in addition, seeks solutions of implementation with regard to its context and the theme that represents, through the understanding of symbolic aspects and also with the reinterpretation of its spaces.